PERPUSTAKAAN SEBAGAI PUSAT SUMBER BELAJAR UNTUK MEWUJUDKAN SEKOLAH YANG UNGGUL - Bella Sonia; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2019)
Abstract: The purpose of this study is to explain: (1) the application of library functions; (2) library services as a center for learning resources; (3) explain the effort to realize superior schools through library services. This research uses qualitative research with research on the types of research that describe and analyze libraries in schools. Data obtained through interviews with several informants consisting of the head of the library, librarians, teachers and students and the head of SMK 4 Malang. The key informant in this study was the head of the library at SMK 4 Malang namely Mr. Mokhamad Rukhan. Checking data in this study uses credibility techniques. By means of research perseverance, triangulation, extension of observation time, and adequacy of reference materials. The conclusions of this study are: (1) schools that implement educational, informative, recreational, research or research functions, and administrative responsibilities; (2) school library services carry out the functions of system development, media services, production, administration, and training. The impact generated by the change and development is an advantage, namely about comfort, the place of facilities, the location of the library locationKeyword: library, learning resources, superior schools Abstrak: Tujuan penelitian ini untuk menjelaskan: (1) penerapan fungsi perpustakaan; (2) layanan perpustakaan sebagai pusat sumber belajar; (3) menjelaskan upaya mewujudkan sekolah unggul melalui pelayanan perpustakaan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus karena mendeskripsikan dan menganalisis secara mendalam tentang perpustakaan di sekolah. Data diperoleh melalui wawancara dengan beberapa informan yang terdiri dari kepala perpustakaan, pustakawan, guru dan siswa dan kepala SMKN 4 Malang. Informan kunci dalam penelitian ini adalah kepala perpustakaan SMKN 4 Malang yaitu Bapak Mokhamad Rukhan. Pengecekan data dalam penelitian ini menggunakan teknik kredibilitas. Dengan cara ketekunan penelitian, triangulasi, perpanjangan waktu pengamatan, dan kecukupan bahan referensi. Simpulan penelitian ini yaitu: (1) sekolah menerapkan fungsi edukatif, informatif, rekreatif, riset atau penelitian, dan tanggungjawab administratif; (2) layanan perpustakaan sekolah menerapkan fungsi pengembangan sistem instruksional, pelayanan media, produksi, administrasi, dan pelatihan. Dampak yang dihasilkan oleh adanya perubahan dan pengembangan tersebut adalah kelebihan yaitu tentang kenyamanan, tempat sarananya, letak lokasi perpustakaanKata Kunci: perpustakaan, sumber belajar, sekolah unggul